Comparative Study of Aerosol Optical Properties along a Megacity - Scagliotti, Ariel Fabricio (2024)
Interest in the study and characterization of aerosols has been growing given its multiple connections with air quality and climate. However, the limited ground-based stations for measurements in many countries are not enough to completely study a big city or a region. Low-cost technology arises as a viable alternative to improve the spatial resolution of measurements. This study aims to demonstrate that the properties of aerosols may change within a megacity and that is advisable to segment measurements according to their characteristics. We measured the optical properties of aerosols in the outskirts of Buenos Aires and compared the data obtained with AERONET data from the city center. This is the first study of its kind in the region. The comparison of concentration, sizes, and types of aerosols shows differences between the sites regardless of the background levels that they share regionally. While the city center has a strong influence from traffic and sea particles and levels of pollution typical of a dense city, the outskirts present several aerosol sources and characteristics of a semirural site with a moderate influence of anthropogenic sources.